2021
DOI: 10.1111/tid.13386
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic gastroenteritis and graft‐versus‐host disease induced by transmission of Norovirus with fecal microbiota transplant

Abstract: Fecal microbiota transplantation (FMT) was performed to decolonize gastrointestinal tract from antibiotic‐resistant bacteria before allogeneic hematopoietic cells transplantation (alloHCT). AlloHCT was complicated by norovirus gastroenteritis, acute graft‐versus‐host disease, and eosinophilic pancolitis. Norovirus was identified in samples from FMT material. Symptoms resolved after steroids course and second norovirus‐free FMT from another donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Moreover, host reaction to Blastocystis spp. colonization may lead to eosinophilic enteritis [ 3 , 4 ]. The prevalence of this parasite has been reported more than 60% in developing countries and between 5% and 20% in developed countries [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, host reaction to Blastocystis spp. colonization may lead to eosinophilic enteritis [ 3 , 4 ]. The prevalence of this parasite has been reported more than 60% in developing countries and between 5% and 20% in developed countries [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…39 Recently, severe complications (sepsis, septic shock, Norovirus infection, bacteremia with drugresistant bacteria) were reported as possibly or certainly related to FMT, also in GI-GvHD patients. 16,42,43 In our study, no immediate, procedure-related complications were observed, but we reported a fatal Adenovirus infection in a patient who had undergone FMT. Of note, we observed a total of three patients with Adenovirus viremia after FMT, two of them with low viremia, asymptomatic, and self-limiting, not needing intervention.…”
Section: Discussionmentioning
confidence: 48%
“…The number of reported infection-related adverse events associated with donor FMT administration is low but transmission of pathogenic microorganisms has been described and can be fatal. 124 , 125 While there is no debate that potential donors of fecal material should undergo stringent screening, the donor screening protocols have been and, for the foreseeable future, will be subject to change as our experience with FMT therapy increases. International guidelines for donor screening protocols, for example as published by the European FMT working group, may help to reduce the variability of screening protocols used in FMT trials.…”
Section: Opportunities For Interventionmentioning
confidence: 99%